Determinants of Brazilian oil exports: an ARDL models approach in the period from 2000 to 2019 - Sousa, Rafael Moraes de; Veríssimo, Michele Polline (Brazilian Keynesian Review, 2022)
It is possible to note a significant increase in primary products share in the Brazilian export basket over the 2000s, with emphasis on crude oil, which becomes the second most exported product in 2019. In this context, this paper investigates the main determinants of Brazilian crude oil exports, using ARDL models with data from 2000 to 2019, in order to infer the sector’s contribution to support the economy reprimarization hypothesis in the long run. The results obtained point out that, in the Brazilian case, the sector benefits, above all, from increases in income (demand) and external prices in the short run. In the long run, the positive effect of foreign income remains combined with the institutional framework improvement and the increased productive capacity given the discovery of Pre-salt reserves.